Role of spinal cyclooxygenase-2 and prostaglandin E2 in fentanyl-induced hyperalgesia in rats. (April 2018) - Li, Q.B.; Chang, L.; Ye, F.; Luo, Q.H.; Tao, Y.X.; Shu, H.H.
Abstract: Background: Accumulated evidence suggests that spinal cyclooxygenase-2 (COX-2) and prostaglandin E2 (PGE2) may be implicated in the development of opioid-induced hyperalgesia. Methods: Rats received subcutaneous fentanyl injections at different doses (20–80 μg kg −1 ), four separate times at 15-min intervals. Some rats only received fentanyl (60 μg kg −1  × 4 doses) with or without surgical incision. Fentanyl-induced hyperalgesia was evaluated via a tail-pressure or paw-withdrawal test. The concentrations of spinal COX-2, EP-1 receptor (EP-1R) mRNA, and PGE2 were measured. The effects of the COX-2 inhibitor, parecoxib (intraperitoneal 10 mg kg −1 ), or the EP-1R antagonist, SC51089 (intraperitoneal 100 μg kg −1 ), on hyperalgesia and spinal PGE2 were examined. Results: Acute repeated injections of fentanyl dose-dependently induced mechanical hyperalgesia, which reached a peak at the 1 st day and persisted for 1–4 days postinjection. This hyperalgesia could be partly or totally prevented by the pretreatment of either parecoxib or SC51089. Consistently, the levels of spinal COX-2 mRNA and PGE2 were also dose-dependently increased, reaching a peak at the first day and persisting for 2 days postinjection. Pretreatment with parecoxib could block the increase in spinal PGE2 and had no effects on spinal COX-2 and EP-1R mRNA. Fentanyl injection enhanced incision-induced mechanical and thermal hyperalgesia. Conclusions: Acute repeated fentanyl administration dose-dependently produced mechanical hyperalgesia and augmented surgery induced postoperative hyperalgesia. This behavioural change was paralleled with an increase in spinal COX-2 mRNA and PGE2 after fentanyl administration. Inhibition of COX-2 or blockade of EP-1R can partly or totally prevent hyperalgesia.